The concept of Sustainable Environments in the UAE: عبد الصمد الخالدي (Al-Academy, 2015)
Over last decade, rapid growth in economic and population accompanied with depletion of the energy resources lead to serious impacts on environment and humanity. This development coupled with active constructions, which in some examples ignore the impact on the environment and human activities. Therefore, principle of sustainability has required in order to reducing this negative impact on the environment and the humanity.In developing countries, it seems that there is a huge gap between the current construction practices and sustainable principle, which need more attention to clarify and define the problems in order to find suitable solutions before it comes more difficult and expensive. The study aims to choose one of the developing countries and analyze its current standing in terms of building sustainability and performance through collecting and analyzing data on construction practices. The purpose of the study is to identify and highlight the main problems in order to evaluate the current situation and propose the possible solutions.A survey have been designed in order to collect data from experts who are involved in constructions projects such as architects, civil engineers, mechanical engineers, electrical and interior designers. A questionnaire will show the strong and feeble points in order to clarify the current practices in terms of sustainability and performance in constructions. The result of the data lead to highlight the significant important of suitability and buildings performance issues in U.A.E to recognize the problems, reduce the obstacles, and try to stimulated solutions and alternatives to improve the current situation, furthermore to be sure that sustainability implementation will be achieved in future